A Single-Label Model to Ensure Data Consistency in Information Security - Bakir, Cigdem (HINDAWI LTD, 2021)
Information security is defined as preventing actions such as unauthorized access and use, modification, and removal of information. It consists of certain basic elements of confidentiality, integrity, and accessibility. There are numerous studies in published literature which have been conducted to ensure information security. However, there is no previous study that covers these three basic elements together. In the present study, a model that includes these three key elements of information security together for big data was proposed and implemented. With this proposed single-label model, a more practical and flexible structure was established for all operations (read, write, update, and delete) performed on a database on real data. In previous studies conducted with a label model, separate labels were used for read-only or write-only operations, and there was no structure that could ensure both confidentiality and integrity at the same time. The present study, however, shows what type of authorization and access control could be established between which processes and which users by looking at a single label for all the operations performed on the data. Thus, in contrast to the previous studies seen in published literature, data confidentiality, data integrity, and data consistency were all guaranteed for all transactions. The results of the proposed single-label model were also shown comparatively by conducting an experimental study of its application. The results obtained are promising for further studies.
Keywords: ACCESS-CONTROL; Computer Science